Drosophila melanogaster Zelda and Single-minded Collaborate to Regulate an Evolutionarily Dynamic CNS Midline Cell Enhancer - Pearson, Joseph C. (2012)
The Drosophila Zelda transcription factor plays an important role in regulating transcription at the embryonic maternal-to-zygotic transition. However, expression of zelda continues throughout embryogenesis in cells including the developing CNS and trachea, but little is known about its post-blastoderm functions. In this paper, it is shown that zelda directly controls CNS midline and tracheal expression of the link (CG13333) gene, as well as link blastoderm expression. The link gene contains a 5’ enhancer with multiple Zelda TAGteam binding sites that in vivo mutational studies show are required for link transcription. The link enhancer also has a binding site for the Single-minded: Tango and Trachealess:Tango bHLH-PAS proteins that also influences link midline and tracheal expression. These results provide an example of how a transcription factor (Single-minded or Trachealess) can interact with distinct co-regulatory proteins (Zelda or Sox/POU-homeodomain proteins) to control a similar pattern of expression of different target genes in a mechanistically different manner. While zelda and single-minded midline expression is well-conserved in Drosophila, midline expression of link is not well-conserved. Phylogenetic analysis of link expression suggests that ~60 million years ago, midline expression was nearly or completely absent, and first appeared in the melanogaster group (including D. melanogaster, D. yakuba, and D. erecta) >13 million years ago. The differences in expression are due, in part, to sequence polymorphisms in the link enhancer and likely due to altered binding of multiple transcription factors. Less than 6 million years ago, a second change occurred that resulted in high levels of expression in D. melanogaster. This change may be due to alterations in a putative Zelda binding site. Within the CNS, the zelda gene is alternatively spliced beginning at mid-embryogenesis into transcripts that encode a Zelda isoform missing three zinc fingers from the DNA binding domain. This may result in a protein with altered, possibly non-functional, DNA-binding properties. In summary, Zelda collaborates with bHLH-PAS proteins to directly regulate midline and tracheal expression of an evolutionary dynamic enhancer in the post-blastoderm embryo.